Glycidamide and cis-2-butene-1, 4-dial (BDA) as potential carcinogens and promoters of liver cancer - An in vitro study. (August 2022) - Gouveia-Fernandes, Sofia; Rodrigues, Armanda; Nunes, Carolina; Charneira, Catarina; Nunes, João; Serpa, Jacinta; Antunes, Alexandra M.M.
Abstract: Acrylamide and furan are environmental and food contaminants that are metabolized by cytochrome P450 2E1 (CYP2E1), giving rise to glycidamide and cis-2-butene-1, 4-dial (BDA) metabolites, respectively. Both glycidamide and BDA are electrophilic species that react with nucleophilic groups, being able to introduce mutations in DNA and perform epigenetic remodeling. However, whereas these carcinogens are primarily metabolized in the liver, the carcinogenic potential of acrylamide and furan in this organ is still controversial, based on findings from experimental animal studies. With the ultimate goal of providing further insights into this issue, we explored in vitro, using a hepatocyte cell line and a hepatocellular carcinoma cell line, the putative effect of these metabolites as carcinogens and cancer promoters. Molecular alterations were investigated in cells that survive glycidamide and BDA toxicity. We observed that those cells express CD133 stemness marker, present a high proliferative capacity and display an adjusted expression profile of genes encoding enzymes involved in oxidative stress control, such as GCL-C, GSTP1, GSTA3 and CAT. These molecular changes seem to be underlined, at least in part, by epigenetic remodeling involving histone deacetylases (HDACs). Although more studies are needed, here we present more insights towards the carcinogenic capacity of glycidamide and BDA and also point out their effect in favoring hepatocellular carcinoma progression. Graphical abstract: Glycidamide and cis-2-butene-1, 4-dial (BDA) prompt liver carcinogenesis and hepatocellular carcinoma progression. Hepatocytes and hepatocellular carcinoma (HCC) cells, which survive glycidamide and BDA toxicity undergo a molecular switch. After exposure to these metabolites, the surviving hepatocytes and HCC cells present an increased proliferative rate and stemness (CD133 + cells). Since glycidamide and BDA promotes the generation of oxidative stress, with increased levels of reactive oxygen species (ROS), a remodeling of the antioxidant systems occurs. A decrease in the expression of genes encoding the catalytic subunit of glutamate-cysteine ligase ( GCL-C ) and glutathione S-transferase π-1 ( GSTP1 ) is seen, being the later a good prognosis cancer marker. Accordingly, the expression of the gene encoding the poor prognosis cancer marker glutathione S-transferase α−3 (GSTA3) increases. In both cell types, the expression levels of catalase encoding gene ( CAT ) fits the expression of their modulators, histone deacetylases 2, 8 and 9 (HDAC 2, HDAC8 and HDAC9). These molecular changes contribute to liver carcinogenesis and to cancer progression as seen by the increased levels of the gene encoding alpha-fetoprotein ( AFP ), the most accurate liver cancer marker. Image 1 Highlights: HepG2 and THLE2 human liver cells were exposed to glycidamide and BDA. Surviving malignant cells exhibit growth advantage, suggesting cancer progression. Carcinogenic initiation was suggested by AFP overexpression in non-cancer cells. Glycidamide and BDA are putative cancer promoters.